Mengelola Risiko Hukum dalam Pengelolaan Tanah: Studi Tentang Praktik Perjanjian Lisan dan Tertulis - Astuti, Ketut; Sukendri, Nengah; Wiguna, Ida Bagus Alit Arta (IAHN Gde Pudja Mataram, 2024)
This research aims to analyse the urgency of written agreements in land management in Oman Nyambu Hamlet, focusing on their benefits in providing legal certainty, preventing disputes, and supporting social stability. Although oral agreements are still commonly used, this research identifies their weaknesses, such as the high risk of conflict and legal uncertainty. Through a juridical-empirical approach involving interviews and document studies, it was found that the main barriers to the implementation of written agreements include low legal literacy, economic constraints, and the influence of local culture. The results show that written agreements not only strengthen the legal position of the parties, but also support the efficiency of land administration. The findings emphasise the importance of legal education, facilitating access to written documents, and digitisation to overcome existing constraints. The study concludes by recommending an integrated approach to improve community legal literacy and promote a more transparent and accountable transformation of land management, to support socio-economic development in rural areas. This study contributes to the development of local needs-based agrarian policies.